I heart you, you haunt me - Schroeder, Lisa (Simon Pulse, 2008)
"Ava can't see or touch him, unless she's dreaming. She can't hear his voice, except for the faint whispers in her mind. Most would think she's crazy, but she knows he's here. Jackson. The boy Ava thought she'd spend the rest of her life with. He's back from the dead, as proof that love truly knows no bounds"--Cover, P. [4].